Physiologically Based Pharmacokinetic (PBPK) Modeling of the Bisphenols BPA, BPS, BPF, and BPAF with New Experimental Metabolic Parameters: Comparing the Pharmacokinetic Behavior of BPA with Its Substitutes - Karrer, Cecile; Roiss, Thomas; von Goetz, Natalie; Gramec Skledar, Darja; Peterlin Mašič, Lucija; Hungerbühler, Konrad (Environmental health perspectives, 2018)
The endocrine disrupting chemical bisphenol A (BPA) has been facing stricter regulations in recent years. BPA analogs, such as the bisphenols S, F, and AF (BPS, BPF, and BPAF) are increasingly used as replacement chemicals, although they were found to exert estrogenic effects similar to those of BPA. Research has shown that only the parent compounds have affinity to the estrogen receptors, suggesting that the pharmacokinetic behavior of bisphenols (BPs) can influence their potency. Our goal was to compare the pharmacokinetic behaviors of BPA, BPS, BPF, and BPAF for different age groups after environmentally relevant external exposures by taking into account substance-specific metabolism kinetics and partitioning behavior. This comparison allowed us to investigate the consequences of replacing BPA with other BPs. We readjusted a physiologically based pharmacokinetic (PBPK) model for peroral exposure to BPA and extended it to include dermal exposure. We experimentally assessed hepatic and intestinal glucuronidation kinetics of BPS, BPF, and BPAF to parametrize the model for these BPs and calibrated the BPS model with a biomonitoring study. We used the PBPK models to compare resulting internal exposures and focused on females of childbearing age in a two-dimensional Monte Carlo uncertainty analysis. Within environmentally relevant concentration ranges, BPAF and BPS were glucuronized at highest and lowest rates, respectively, in the intestine and the liver. The predominant routes of BPS and BPAF exposure were peroral and dermal exposure, respectively. The calibration of the BPS model with measured concentrations showed that enterohepatic recirculation may be important. Assuming equal external exposures, BPS exposure led to the highest internal concentrations of unconjugated BPs. Our data suggest that the replacement of BPA with structural analogs may not lower the risk for endocrine disruption. Exposure to both BPS and BPAF might be more critical than BPA exposure, if their respective estrogenic potencies are taken into account. https://doi.org/10.1289/EHP2739.